Choral voices ethnographic imaginations of sound and sacrality - Chatterjee, Sebanti (Bloomsbury Academic, 2023)
The first account of the public life of choral music shaped by imperialistic, cosmopolitan and indigenous characteristics in the regions of Goa in Western India and Shillong in the North-Eastern part of India"--